Most Current Issues and Perspectives of the Urban Slum Problem in Kenya - Solymári, Dániel; Czirják, Ráhel (Nemzet és Biztonság : biztonságpolitikai szemle, 2024)
The paper examines the largest-scale historical slum development program, that has been running in Kibera, the biggest slum of Kenya, since the turn of the millennium: Kenya Slum Upgrading Programme (KENSUP) and its two projects Kibera Integrated Water, Sanitation and Waste Management Project (K-WATSAN) and Kibera Slum Upgrading Initiative (KSUI). The paper synthesises the available literature to examine the extent to which the objectives originally set for 2020 have been achieved. The study found that K-WATSAN was successful both in terms of actively involving the locals and improving their life conditions. However, KSUI did not utilise the experiences gained regarding the significance of community participation. Consequently, structural flaws emerge that call into question the actual fulfilment of the programme's goals, as well as the programme's sustainability.